Taxonomia de rotíferos monogonontas da planície de inundação do alto rio Paraná (MS/PR). - Joko, Ciro Yoshio (2011)
The phylum Rotifera has approximately 2030 known species (Segers, 2007) occurring with great richness and abundance in the majority of inland water bodies. Among tropical and subtropical environments, floodplains stand out by presenting high productivity and aquatic biodiversity. Based on the high richness of rotifers in these environments, the researchers proposed the hypothesis that ?(sub) tropical floodplains are the habitats with the highest richness of rotifers worldwide?. In Brazil, the highest diversity of rotifers takes place in regions subjected to floodings, such as the Paraná River basin. This basin presents the highest richness of rotifers already recorded for Brazil, with 304 taxa, in turn the Amazon region has around 300 taxa, and the pantanal matogrossense, 200 taxa. It is important to note that there are few taxonomic studies with rotifers in these regions. The present study aimed at compiling the taxonomic knowledge about rotifers of the SubClass Monogononta from the Upper Paraná River floodplain, an ecosystem with great relevance due to the highest richness of rotifer taxa in Brazil, result from nearly 20 years of researches made by the Laboratory of Zooplankton of the Núcleo de Pesquisas em Limnologia, Ictiologia e Aqüicultura (Nupélia), of the State University of Maringá. The organisms examined belong to samples of the collection of the Laboratory of Zooplankton of Nupélia. The samples were sorted, and the organisms found were separated, identified, illustrated, and characterized (morphology and morphometry) to the lowest possible taxonomic level. The taxonomic record of 74% of rotifer taxa from the floodplain is considered representative; the presence of numerous littoral species in this study evidences that the rotifer richness of this region is still underestimated, in this way, this number may considerably increase in further studies directed to littoral fauna.